Influencia de los factores emocionales en el rendimiento de los trabajadores (2019)
The operation of the companies is usually the same as the employees that each one of the employees that make up said organizations possess; Therefore, the objective of this work is aimed at influencing the emotions of employees in their work performance, based on the methodology of bibliographic review. Companies are beyond an academic degree or work experience; currently, we take into account the talents of the people who make up the organizations, because the attitudes of employees diversify the essence of the companies become strong structures that can be fickle and resistent in adverse situations (financial deficit, little demand for production, etc.) expected in the functioning of the entity. Therefore, an expansion of qualities to be taken into account for the performance of the different positions in the companies is created